Optimal scheduling of integrated energy system with gas–liquid phase change carbon dioxide energy storage considering multi-layer low-carbon benefits - Weiguo Li; Guangyao An; Tingting Cai; Qingying Yang (Scientific Reports)
Abstract Integrating a carbon dioxide energy storage system (CES) with an integrated energy system (IES) can significantly enhance renewable energy utilization, reduce carbon emissions, and improve both economic and environmental performance. This paper proposes an optimal scheduling strategy for a gas–liquid phase change CES coupled with wind and solar generation, considering multi-layer low-carbon benefits. At the system structural level, an IES operation framework integrating carbon capture and storage (CCS) and power-to-gas (P2G) technologies is developed to fully exploit the potential of CO2 capture and utilization. At the technical level, a mathematical model of gas–liquid phase change CES coupled with wind and solar is established to enhance renewable energy absorption. Based on a life cycle cost model of gas–liquid phase change CES, the economic and low-carbon advantages of CES are pointed out. By introducing a stepped carbon trading mechanism at the policy level, an IES scheduling model with the goal of considering the comprehensive economic optimization of low-carbon benefits is established. The results of the scene show that the proposed method reduces the system carbon emissions by 33.26%, increases the new energy consumption rate by 3.54%, and reduces the total operating cost of the system by 24.30%, which lays a theoretical foundation for the research of environmentally friendly IES.